PENYAJIAN DATA SPASIAL DISTRIBUSI KASUS TUBERKULOSIS DI PUSKESMAS GEDONGTENGEN YOGYAKARTA - , PRASTIWI, Arief Kurniawan, SKM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: A case of tuberculosis in Yogyakarta City Health Department in 2012 as many as 407, with 205 cases came from the city of Yogyakarta and 202 cases of tuberculosis are from outside Yogyakarta, for the year 2013 there were 243 new cases, and in most cases Gedongtengen health center. The spread of tuberculosis can be presented in the form of spatially using geographic information system (GIS). Objective: Presenting spatial data distribution Gedongtengen tuberculosis in health center in January, February 2014, by sex, age group, population density, distance buffer with residential health center patients. Methods: This was a descriptive study using a qualitative approach tuberculosis patient population in Yogyakarta Gedongtengen Health Center. Data collection techniques and documentation studies using data analysis techniques using data reduction, data display, conclusion. Results: Case tuberkulosi in January and February 2014, there were 7 cases are scattered in the Village Pringgokusuman and Sosromeduran, the number of male patients and 4 female 3. Based on the known age group 30-45 age group amounted to 2 patients, aged 45-60 amounted to 4 patients, aged > 60 numbered 1 patient, buffer analysis to know the distance to the health center patients found shelter at a distance of 300 m, 400 m, 500 m, 600 m with a density of population in the region Village Pringgokusuman 0.269 people per km2 and Sosromeduran 0.189 people per km2 Conclusion: Distribution of tuberculosis cases in the region Gedongtengen highest in Sub Pringgokusuman found that 71% of the number of male patients reached 57%, and highest in the 45-60 age group is 57.14%. Buffer distances to health centers where people with the highest living at a distance of 500 m which reaches 42.8% and spread the population density 269 people per km2 contained in kelurah Pringgokusuman, which can be seen clearly in the form of spatial data.